Butt, George (Bryant's Cove) and Andrew and Elizabeth Parsons (Freshwater). Interviews with George Butt and Andrew and Elizabeth Parsons. - Baccalieu Trail Heritage Corporation (1995)
This interview is part of a series of filmed oral histories, collected by the Baccalieu Trail Heritage Corporation, from elders who grew up in the area. The Baccalieu Trail Heritage Corporation is a not-for-profit organization dedicated to preserving, promoting and protecting the heritage of the Baccalieu Trail Region. This project collected memories of living and working in the area, going to school, children’s games, home remedies, the first modes of transportation, supernatural beliefs, traditional industries and calendar customs and celebrations. The first interview is with George Edward Butt of Bryant's Cove. The interviewer is Terry Shea and the interview took place May 13, 1992. The second interview is with Andrew and Elizabeth Parsons of Freshwater and took place January, 1995. The interviewer is Rowena Smith. From [00:01-55:38] is the interview with George Edward Butt of Bryant's Cove. From [55:47-1:30:14] is the interview with Andrew and Elizabeth Parsons of Freshwater.